Comparative Study on Outcome of Non-invasive Ventilation in Patients with Acute Exacerbation of COPD Admitted in General Ward vs. High Dependency Unit - Debabani Biswas; Susmita Kundu; Arnab Bera; Atin Dey; Subrata Rath; Amitava Pal (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Non-Invasive Ventilation (NIV) is getting popularity in management of acute exacerbation of COPD with hypercapnic respiratory failure because of its effectiveness. However, there is still a dilemma regarding the site of initiation of NIV. There are several publications comparing outcome of NIV in highly sophisticated Intensive Care Units (ICU) and general ward in western literature, there is paucity of data from this part of the world. Considering unavailability of beds in highly monitored ward, the studies related to feasibility and acceptability of using NIV in general ward might be helpful in reducing suffering of distressed COPD patients. Aim: To assess the outcome and relative feasibility of NIV use in general ward and High Dependency Unit (HDU) in hypercapnic respiratory failure due to Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) in a tertiary care hospital. Materials and Methods: It was a prospective observational study. Patients admitted with AECOPD in HDU and general ward, satisfying all inclusion and exclusion criteria, over a period of six months were recruited as study population. All the patients received NIV along with other conventional treatment protocol. The outcome of NIV was noted in terms of frequency of complications, duration of hospital stay and need for mechanical ventilation. The statistical analysis was done using SPSS Minitab software version 15.1.0. Results: A total of 70 patients, age ranging from 45-89 years, were included. A 32 patients were put on NIV in general ward while 38 in HDU, depending on availability of bed. There were no significant differences in the clinical parameters at the time of initiation of NIV between the two subsets except the total leukocyte count and the frequency of occurrence of exacerbation in last one year. The outcome of NIV use as analysed found no significant difference in average duration in hours ‘on NIV’ (p=0.088) among patients who were successfully treated with NIV. Similarly the complication profile and overall failure rate comparable was (p=0.515) between the two subsets. Conclusion: The NIV is as effective in management of AECOPD with hypercapnic failure in HDUs and less monitored general medical ward in face of non-availability of ICU beds, particularly in a resource constrained setting.